Fatty Acid Synthetase of Spinacia oleracea Leaves - Shimakata, Takashi (1982)
The molecular organization of fatty acid synthetase system in spinach (Spinacia oleracea L. var. Viroflay) leaves was examined by a procedure similar to that employed for the safflower system (Carthamus tinctorius var. UC-1). The crude extract contained all the component activities (acetyl-CoA:ACP transacylase, malonyl-CoA:ACP transacylase, β-ketoacyl-ACP synthetase, β-ketoacyl-ACP reductase, β-hydroxyacyl-ACP dehydrase, and enoyl-ACP reductase [I]) involved in the synthesis of fatty acids, but enoyl-ACP reductase (II) present in safflower seeds extract could not be detected spectrophotometrically. By polyethylene glycol fractionation followed by several chromatographic procedures, i.e. Sephadex G-200, hydroxyapatite, and blue-agarose, the component enzymes were clearly separated from one another. Properties of β-ketoacyl-ACP reductase, β-hydroxyacyl-ACP dehydrase, and enoyl-ACP reductase (I) from spinach were compared with the same enzymes in safflower seeds and Escherichia coli. From these results, it was concluded that the fatty acid synthetase system of spinach leaves, as well as that of safflower seeds, was nonassociated and similar to the Escherichia coli system.